PROSES PELAKSANAAN SISTEM PRE-BOOKING TIKET GARUDAINDONESIA TRAVEL FAIR (GATF) 10-12 MARET 2017 DI JAKARTA OLEHPT. AERO GLOBE INDONESIA (AEROTRAVEL) GUNUNG SAHARI - Syaukani, Muhammad Ariq; Tasran, Chaidir; Pranita, Diaz (UI Scholars Hub, 2017)
The focus of this study is the result of thoughts and data collection the authors who have undergone work practices in PT Aero Globe Indonesia (Aerotravel) Gunung Sahari. At the end of this Paper discusses the Tasks regarding the process of implementation of the system of Pre-Booking tickets Garuda Travel Fair 10-12 March 2017 Jakarta conducted by PT. Aero Globe Indonesia (Aerotravel) Gunung Sahari. Starting from filling the form PreBooking tickets Garuda Travel Fair by the prospective purchaser of the ticket, the process of booking and ticket issued promo Lions Travel Fair 10-12 March 2017 by Ticketing Staff of PT Aero Globe Indonesia. Obstacles, barriers and solutions in the process of implementing a system of Pre-Booking are also discussed on this final paper assignment.